2021
DOI: 10.21037/atm-21-542
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of tenosynovial giant cell tumors, synovial chondromatosis, and synovial sarcoma: analysis and report of 53 cases

Abstract: Background: Tenosynovial giant cell tumors (TGCTs), synovial chondromatosis (SC), and synovial sarcoma (SS) exhibit similarities in clinical features and histochemical characteristics, and differential diagnosis remains challenging in clinical practice.Methods: Data were collected from the pathology database of Shanghai Ninth People's Hospital regarding patients who underwent surgery from 2010 to 2019 with histologically confirmed TGCTs, SC, and SS.Demographic and clinicopathological data of these patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In this study, we found molecular sharing between TGCT, Osteoarthritis, and Synovial Sarcoma. This implies that these diseases may have similar pathogenesis or disease backgrounds, which may help us detect and diagnose these diseases earlier, especially Synovial Sarcoma ( 36 ), thereby making treatment more timely and effective.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found molecular sharing between TGCT, Osteoarthritis, and Synovial Sarcoma. This implies that these diseases may have similar pathogenesis or disease backgrounds, which may help us detect and diagnose these diseases earlier, especially Synovial Sarcoma ( 36 ), thereby making treatment more timely and effective.…”
Section: Discussionmentioning
confidence: 99%